Managers’ perceptions of spirituality in the context of brazilian organizations towards sustainability - Garlet, Valéria; Madruga, Lúcia Rejane da Rosa Gama; Barros, Thiago Antônio Beuron Corrêa de; Cezar, Fernando Vieira; Beuron, Bruno Mello Correa de Barros (Revista de Administração da UFSM, 2024)
Objective: To identify managers’ perceptions of spirituality with a view to sustainability in Brazilian organizations. Method: 10 interview groups were carried out with 35 managers from different types of organizations (private companies, public universities, private universities, city halls, Non-Governmental Organizations (NGOs), civil police, and military police). The interview was developed with the open question: What do you understand by spirituality? The qualitative approach to the data was based on the thematic analysis technique (Braun & Clarke, 2006). Findings: Regarding the theme Spirituality, 19 categories were identified in the interviewees’ statements: energy, purpose/meaning, connection, empathy, leadership, values, relationships between people, care, faith, relationship with religion, decision, welfare/well-being, transcendence/beyond the material, God/universe, strength, resilience/improvement, belief/beliefs, work/organization, harmony/balance. It was identified, according to the interviewees’ statements, that spirituality is a way of living based on an energy, linked or not to religion, which understands human transcendence, which provides well-being, which helps to overcome challenges and difficulties of life, which welcomes the other, conducts work valuing people and looking at them in their entirety through values, beliefs, faith, God, self-knowledge, connection with oneself and with something greater, and the constant search for purpose and meaning for life. Originality: Understanding, from the perception of managers of different types of organizations, how spirituality can impact sustainability is interesting both from the point of view of the employee and the organization and from the point of view of the future, society, and the Planet.